Analysis of the Occurrence of the Ash Maples in the Town of Tirkšliai - Garalė, Ernesta (Jaunųjų mokslininkų darbai, 2023)
The study analyses the occurrence of Ash Maples (Acer negundo L.) in the town of Tirkšliai, which is located in the municipality of Mažeikiai district. The assessment survey was carried out in September–October 2023. The inventory of the Ash Maples was carried out using a route method, recording the coordinates and the conditions of the sites: area, projection coverage of individuals, level of urbanisation of the ecotope, biotope, assessment of whether or not the area of the site was mown, intensity of use of the area where the site is located. The ontogeny stage shall be assessed on the basis of the vegetative and generative characters of the ash-leaved maples and the height of the trees. The height of the individuals of the Ash Maple was determined visually, in metres, by assessing the entire length of the above-ground part of the tree. In total, 14 sites with ash-leaved maples were identified as well as 10 sites with trees of juvenile age. Most of the sites were found in grassland (64 %), 79 % in roadsides, by intensity of land use the highest number of sites were found in unused land (43 %), 50 % of the sites are not mown. It is therefore evident that the occurrence of big-leaved maple trees is higher in less maintained areas.